The Encyclopedia of animal ecology - Moore, Peter D. (New York : Facts on File Publications, 1987)
Photographs, diagrams and text introduce the ideas and concepts which ecologists have developed to describe and explain the world of nature.
"An Equinox book"--T.p. verso.
Includes index.
Bibliography: p. 144.
Wilson's Senior High School.
Young Adult.
Young Adult
Keywords: Animal ecology; Animal ecology